Primes, Primitives, and Pythagoras - Wood, Taylor; Odom, Jenna (Ohio Journal of School Mathematics, 2018)
The authors explore the connections between prime factorizations and primitive Pythagorean triples, investigating special cases of primitive triangles in order to predict when hypotenuse lengths produce more than one distinct triangle. The authors discuss the usefulness of the method in secondary school classrooms.